2012
DOI: 10.1371/journal.pone.0043963
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Methylene Blue on Microglia-Induced Inflammation and Motor Neuron Degeneration in the SOD1G93A Model for ALS

Abstract: Mutations in SOD1 cause hereditary variants of the fatal motor neuron disease amyotrophic lateral sclerosis (ALS). Pathophysiology of the disease is non-cell-autonomous, with toxicity deriving also from glia. In particular, microglia contribute to disease progression. Methylene blue (MB) inhibits the effect of nitric oxide, which mediates microglial responses to injury. In vivo 2P-LSM imaging was performed in ALS-linked transgenic SOD1G93A mice to investigate the effect of MB on microglia-mediated inflammation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 57 publications
1
42
0
1
Order By: Relevance
“…Our experiments demonstrated that although these four compounds function within the UPR ER they operate through different branches of this pathway to achieve neuroprotection. There is growing evidence for a protective role of methylene blue against multiple forms of neurodegeneration including mTDP-43 Yamashita et al, 2009), mFUS , mutant SOD1 (Dibaj et al, 2012) mutant polyglutamine proteins (Sontag et al, 2012), and MB has shown promising effects in a Phase II clinical trial for AD (Gura, 2008). MB is not protective in adult SOD1 (Lougheed and Turnbull, 2011) or TDP-43 mice (Audet et al, 2012) and we found diminished effect on worms , and no activity in zebrafish (data not shown) after the phenotypes have been established, indicating that these compounds may not be useful for treating the disorder.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our experiments demonstrated that although these four compounds function within the UPR ER they operate through different branches of this pathway to achieve neuroprotection. There is growing evidence for a protective role of methylene blue against multiple forms of neurodegeneration including mTDP-43 Yamashita et al, 2009), mFUS , mutant SOD1 (Dibaj et al, 2012) mutant polyglutamine proteins (Sontag et al, 2012), and MB has shown promising effects in a Phase II clinical trial for AD (Gura, 2008). MB is not protective in adult SOD1 (Lougheed and Turnbull, 2011) or TDP-43 mice (Audet et al, 2012) and we found diminished effect on worms , and no activity in zebrafish (data not shown) after the phenotypes have been established, indicating that these compounds may not be useful for treating the disorder.…”
Section: Discussionmentioning
confidence: 99%
“…-mutant TDP-43 Yamashita et al, 2009) -mutant FUS -mutant SOD1 (Dibaj et al, 2012) -mutant polyglutamine (Sontag et al, 2012) Phase II clinical trial for Alzheimer's disease (Gura, 2008) Salubrinal -Inhibits eIF2α phosphatases in the UPR ER pathway (Boyce et al, 2005). -Disrupts the PP1 complex to increase phosphorylation of eIF2α (Jousse et al, 2003) Functions inside the PERK pathway but seems not restricted to the UPR: continues to reduce mTDP-43 paralysis when PERK absent Effective in reducing mutant SOD1 toxicity in a mouse model of ALS ).…”
Section: Protein Solubilitymentioning
confidence: 99%
“…Inflammation basically, serves as a key factor in course of the disease with effective involvement at two different stages i.e., initially in a protective mode, later causing neurotoxicity [76]. Experimental data from lumbar spinal cord SOD1G93A mice was compared with end stage SOD1G93A mice microglia and the result showed loss of motor neurons in end group, which revealed the direct influence of inflammation in ALS pathology [77,78]. Similar experiment also proved the involvement of interleukin-4 (IL-4) along with insulin like growth factors 1 (IGF-1), which considerably increases microglia expression [77,78].…”
Section: Amyotrophic Lateral Sclerosismentioning
confidence: 99%
“…Experimental data from lumbar spinal cord SOD1G93A mice was compared with end stage SOD1G93A mice microglia and the result showed loss of motor neurons in end group, which revealed the direct influence of inflammation in ALS pathology [77,78]. Similar experiment also proved the involvement of interleukin-4 (IL-4) along with insulin like growth factors 1 (IGF-1), which considerably increases microglia expression [77,78]. In advanced stages of ALS, pro-inflammatory properties are observed, as rise in interleukin-1 beta (IL-1β) and tumor necrosis factor α (TNF-α) in spinal cord [76].…”
Section: Amyotrophic Lateral Sclerosismentioning
confidence: 99%
“…However, the mechanism of neurodegeneration, except for clinical evidences, through C9ORF72 repeat expansions still remains to be elucidated. Two studies reported that microglia is associated with motor impairment in ALS (Boillée et al 2006;Dibaj et al 2012). Thus, these findings support the possibility that GARS mutation-induced neuroinflammation is a mechanism for GARS-associated neuropathies, similar to that of neuronal degeneration in ALS.…”
Section: Adenoviral Vector-mediated Animal Models For Motor Impairmentmentioning
confidence: 99%